To fast or not to fast?; Pangulu Ki Amad Kategan challenges his sultan in the Sĕrat Nitik Sultan Agung - Bogaerts, Els (UI Scholars Hub, 2021)
The Sĕrat Nitik Sultan Agung texts relate how Sultan Agung (r. 1613-1645) in a miraculous way conquers the surrounding world. He subjugates its inhabitants to Mataram and converts them to Islam. The selected fragment is an interesting example of how the sultan – refusing to fast during the month of Shawwāl – impresses the people in his environment with his supernatural power, and in particular Ki Amad Kategan, his pangulu, who tries to match his strength with that of the sultan. The two characters engage in a dispute on Islamic matters. Firstly, I discuss the figure of Ki Amad Kategan and the function of this excerpt in the Nitik Sultan Agung tales. Secondly, I present variant readings of the story. The comparison of the three versions touches on features of narrative structure, content and style, language use, and target audiences.